A hydrophobically modified molecularly imprinted fluorescent sensor and a method of making the same

CN122901138APending Publication Date: 2026-10-13JIMEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610924438.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,研究表明,三苯甲烷类染料及其隐色代谢物具有潜在的致癌、致畸和致突变风险,对生态环境和人体健康构成严重威胁

Benefits of technology

(1)本申请提供的分子印迹荧光传感器采用长链硅烷基与二氧化硅网络协同改性策略。其中,二氧化硅网络与包载荧光离子对的PMMA形成有机-无机杂化网络,显著增强复合功能涂层的结构致密性和抗溶剂溶出能力;长链硅烷基接枝于传感器表面,构筑疏水屏障。二者协同作用,既提升了复合功能涂层的结构稳定性,又赋予其抵抗有机试剂冲刷的能力,确保传感器在复杂检测环境中信号稳定可靠。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122901138A_ABST
    Figure CN122901138A_ABST
Patent Text Reader

Abstract

The application provides a molecular imprinting fluorescent sensor and a preparation method thereof. The molecular imprinting fluorescent sensor comprises a paper substrate and a composite functional coating; the composite functional coating comprises a molecular imprinting polymer, a fluorescent ion pair and an organic-inorganic hybrid network; the molecular imprinting polymer takes triphenylmethane compounds as template molecules; the fluorescent ion pair forms a fluorescence resonance energy transfer system with the triphenylmethane compounds; the organic-inorganic hybrid network is composed of a silica network and polymethyl methacrylate; and the composite functional coating further comprises grafted C 8‑18 silane groups. The molecular imprinting fluorescent sensor is simple in operation, rapid in response, stable and reliable in signal in a complex detection environment, has good light stability and storage stability, meets the demand of batch detection of actual samples, and has good application potential and popularization value in the field of food safety rapid detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fluorescence sensing technology, specifically relating to a molecularly imprinted fluorescence sensor, and more particularly to a molecularly imprinted fluorescence sensor based on an organic-inorganic hybrid network and hydrophobic modification. Background Technology

[0002] Triphenylmethane dyes (such as crystal violet and malachite green) were once widely used as bactericides and preservatives in aquaculture due to their low cost and strong tinting strength. However, studies have shown that triphenylmethane dyes and their leuco metabolites pose potential carcinogenic, teratogenic, and mutagenic risks, seriously threatening the ecological environment and human health. Although many countries, including my country, have explicitly banned the use of these dyes in aquaculture, their excellent bactericidal effects and low cost mean that illegal use continues unabated, leading to increasingly prominent problems with the residue of these dyes in aquatic products. Therefore, developing rapid, sensitive, and convenient detection methods for triphenylmethane dyes is of great significance for ensuring the quality and safety of aquatic products and protecting consumer health.

[0003] Molecular imprinting technology, with its advantages of strong specificity, good structural pre-determinacy, and high physicochemical stability, shows broad application prospects in the selective enrichment and detection of trace pollutants in complex samples. The core advantage of this technology lies in template customizability—by changing the template molecule, imprinted holes that are complementary to the target analyte in size, shape, and functional groups can be reconstructed while keeping the synthesis system essentially unchanged. However, in actual sample pretreatment processes, the use of organic reagents (such as ethanol and acetonitrile) is unavoidable, which places higher demands on the structural stability and signal reliability of the sensing layer.

[0004] To address the aforementioned issues, it is necessary to develop a molecularly imprinted fluorescence sensor that combines high stability, high sensitivity, and resistance to organic reagent erosion. Summary of the Invention

[0005] The purpose of this application is to provide a novel molecularly imprinted fluorescent sensing material with specific recognition ability for triphenylmethane dyes, providing a new detection method for rapid screening of triphenylmethane dye residues in aquatic products.

[0006] To achieve the above objectives, this application provides the following technical solution: A molecularly imprinted fluorescence sensor comprising a paper substrate and a composite functional coating; The composite functional coating contains molecularly imprinted polymers, fluorescent ion pairs, and an organic-inorganic hybrid network; The molecularly imprinted polymer uses triphenylmethane compounds as template molecules; The fluorescent ion pair forms a fluorescence resonance energy transfer system with the triphenylmethane compound; The organic-inorganic hybrid network is composed of a silica network and polymethyl methacrylate; The composite functional coating also contains grafted C 8-18 Silyl group.

[0007] This application also provides the following technical solutions: The aforementioned method for preparing the molecularly imprinted fluorescent sensor.

[0008] The technical solution provided in this application has the following beneficial effects: (1) The molecularly imprinted fluorescence sensor provided in this application employs a synergistic modification strategy of long-chain silanes and silica networks. Specifically, the silica network forms an organic-inorganic hybrid network with PMMA carrying fluorescent ion pairs, significantly enhancing the structural density and solvent resistance of the composite functional coating; the long-chain silanes are grafted onto the sensor surface to construct a hydrophobic barrier. This synergistic effect not only improves the structural stability of the composite functional coating but also endows it with the ability to resist the erosion of organic reagents, ensuring stable and reliable signal transmission from the sensor in complex detection environments.

[0009] (2) The molecularly imprinted fluorescence sensor provided in this application can construct a molecularly imprinted polymer with specific recognition capabilities in situ on a paper substrate using sol-gel technology. Combined with the fluorescence resonance energy transfer (FRET) mechanism between fluorescent ion pairs and the target analyte, it can achieve selective recognition and fluorescence quenching detection of template molecules. Taking crystal violet (CV) as an example, the linear detection range of the fluorescence sensor provided in this application is 0.1 μmol / L to 20 μmol / L, and the detection limit is as low as 0.040 μmol / L. The sensor can also achieve visual semi-quantitative detection through fluorescence color change under ultraviolet light, which is simple to operate and has a rapid response. The sensor has achieved a high spiked recovery rate (84.06% to 94.34%) and a low relative standard deviation (0.95% to 6.65%) in actual aquatic product testing, proving its good application potential and promotion value in the field of rapid food safety detection.

[0010] (3) The molecularly imprinted fluorescence sensor provided in this application stably immobilizes fluorescent ion pairs in a composite functional coating, exhibiting good photostability and storage stability, meeting the needs of batch detection of actual samples. Experiments show that the sensor can be continuously irradiated under ultraviolet light for 10 hours without significant change in fluorescence intensity, and can still maintain about 90% of the original fluorescence intensity after being stored in the dark for 30 days. Attached Figure Description

[0011] Figure 1 This is a schematic diagram illustrating the construction principle of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor.

[0012] Figure 2 The results are as follows: (A, fluorescence excitation and emission spectra of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor; B, UV spectrum of CV and fluorescence spectrum of RhB).

[0013] Figure 3 The results are for feasibility verification (A, fluorescence spectrum of CV detected by OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor; B, fluorescence spectrum of CV detected by OTS / TEOS-PMMA@RhB-F5TPB NIPs fluorescence sensor).

[0014] Figure 4 The effects of adding different fluorescence sensors to ethanol (top image under UV light, bottom image under visible light).

[0015] Figure 5 Scanning electron microscope images (A, blank filter paper; B, TEOS-PMMA@RhB-F5TPB MIPs; C, OTS-PMMA@RhB-F5TPB MIPs; D, OTS / TEOS-PMMA@RhB-F5TPB MIPs).

[0016] Figure 6 The results show the selectivity test results (A, a comparison of selectivity for template and non-template compounds; B, visualization of the MIPs and NIPs fluorescence sensor test results under UV light).

[0017] Figure 7 The results of the linear analysis are shown in Figure 1 (A, fluorescence emission spectra of the fluorescence sensor in the presence of different concentrations of CV; B, linear fitting of the fluorescence quenching efficiency of the fluorescence sensor to CV; C, visualization under UV light).

[0018] Figure 8 The results are for fluorescence stability tests (A, under UV light, 0-10 h; B, placed in the dark, 0-30 days).

[0019] Figure 9 Optimization of OTS concentration (A, Effect of OTS concentration on fluorescence intensity; B, Effect of OTS concentration on fluorescence quenching efficiency).

[0020] Figure 10 Eluent optimization (A, Effect on fluorescence response under UV light; B, Effect on fluorescence quenching efficiency).

[0021] Figure 11 Optimization of TEOS addition amount (A, effect on fluorescence intensity; B, effect on fluorescence quenching efficiency).

[0022] Figure 12 Optimization of TEOS hydrolysis time (impact on fluorescence quenching efficiency).

[0023] Figure 13 Optimization of PMMA concentration (A, effect on fluorescence intensity; B, effect on fluorescence quenching efficiency). Invention Details 1. Terminology Explanation All patents and other publications cited herein are incorporated herein in their entirety. In the event of any conflict between any description of terminology herein and any document incorporated herein by reference, this document shall prevail.

[0025] Numerical ranges can be represented by a hyphen "-" or a tilde "~". Unless otherwise stated, the range should be understood to encompass both the endpoint values ​​and any values ​​in between. There are no particular restrictions on the type of numeric values ​​within the range, including but not limited to integers, decimals, fractions, percentages, etc., unless explicitly excluded by the context or a particular numeric type is technically unavailable. The type of numeric values ​​within the range is not limited by the specific representation of the endpoints.

[0026] The terms “including,” “containing,” and similar expressions have a non-restrictive meaning.

[0027] "Optional" is used to indicate that a certain feature (including but not limited to components, steps, parameters or structures) may be present in some embodiments, but may not appear in other embodiments, thereby providing technical flexibility for different implementations without departing from the core concept of the present invention.

[0028] "Any combination" of the enumeration items means any two or more of the enumeration items that coexist or are used together, including but not limited to any two combinations, any three combinations, any more items, and combinations of all the enumeration items, unless the context explicitly excludes it or a particular combination is technically impossible.

[0029] The use of labels such as a), b), i), ii), 1), 2), S1, S2, etc. to number the steps of a method is only for the convenience of description and reading, and does not mean that the corresponding steps must be performed in the order of the numbers, unless the text explicitly states or the information in the text can be clearly inferred that there is a logical or temporal relationship between specific steps.

[0030] The number of carbon atoms in a chemical structure (e.g., groups, molecules, fragments) can be represented by a numerical value placed at the "C" subscript position, and by default, it does not include the contribution of substituents. For example, "C 8-18 Silyl groups refer to silyl groups with 8-18 carbon atoms, including but not limited to octylsilyl, dodecylsilyl, hexadecylsilyl, octadecylsilyl, etc.

[0031] The term "silane" as used herein can be considered as a silicon-containing functional group formed by the loss of at least one hydrogen atom from a silane molecule. The silane may be optionally substituted, i.e., substituted or unsubstituted. "Substituted" means that the silane contains one or more substituents, as long as the presence of the substituents does not affect the smooth implementation of this invention. There are no particular limitations on the method of grafting silane onto the surface of a paper-based fluorescent sensor; silanization treatments known in the art can be used. For example, the hydrolysis and condensation reaction of a silane coupling agent (e.g., octadecyltrichlorosilane, octadecyltrimethoxysilane, dodecyltrichlorosilane, etc.) can be used to form siloxane bonds with hydroxyl groups on the sensor surface (including alcohol hydroxyl groups and silanyl hydroxyl groups in the substrate and coating), thereby achieving silane grafting. Adjacent silicon atoms can also form siloxane crosslinks (Si-O-Si). There are no particular limitations on the grafting site, including but not limited to the surface of the paper substrate, the surface of the composite functional coating, and its interior. The long-chain silane grafted onto the sensor surface can self-assemble to form a hydrophobic barrier, achieving the effects of resisting organic solvent erosion and preventing the dissolution of fluorescent substances.

[0032] The "molecularly imprinted polymers" described in this article refer to polymers formed after polymerization around a template molecule followed by the removal of the template molecule, which are complementary to the template molecule in terms of spatial structure and binding sites. Molecularly imprinted polymers can selectively recognize and rebind template molecules or their structural analogues, thereby achieving specific capture.

[0033] The term "template molecule" as used in this article refers to a target compound used to construct specific recognition sites in a polymer matrix during the synthesis of molecularly imprinted polymers. The template molecule is pre-bound to a functional monomer through covalent or non-covalent interactions and is then eluted after polymerization, leaving imprinted cavities in the polymer that match its shape, size, and functional group arrangement.

[0034] The "fluorescence resonance energy transfer system" described herein refers to a non-radiative energy transfer system consisting of a donor and an acceptor capable of fluorescence resonance energy transfer (FRET). Typically, FRET requires the following conditions to occur: (i) there is significant overlap between the emission spectrum of the donor and the absorption spectrum of the acceptor; (ii) the distance between the donor and acceptor is within the range of 1-10 nm (i.e., within the Förster radius); and (iii) the donor has a high fluorescence quantum yield, and the transition dipole orientation of the donor and acceptor is appropriate. The molecularly imprinted fluorescence sensor provided in this application uses triphenylmethane compounds as FRET acceptors and selects fluorescent ion pairs with suitable emission spectra as FRET donors. Under excitation light, the donor emits characteristic fluorescence. When the molecularly imprinted layer captures and enriches the target analyte, the distance between the donor and acceptor is less than the Förster radius, triggering the FRET effect and causing a significant decrease in the fluorescence intensity of the fluorescent ion pair. By measuring the degree of fluorescence quenching, the content of triphenylmethane compounds in the sample can be quantitatively detected.

[0035] The term "fluorescent ion pair" as used herein refers to an associated system containing at least one fluorescent chromophore, formed by the electrostatic interaction of anions and cations. In this application, the fluorescent ion pair consists of an ion (which may be a cation or anion) with fluorescent emission properties and a large, weakly coordinated counter ion with opposite charge; wherein the counter ion effectively prevents aggregation-induced quenching (ACQ) of the fluorescent ion under high loading conditions. As an example, the fluorescent ion pair may consist of a fluorescent dye (e.g., Rhodamine B and its derivatives, cyanine dyes Cy3 / Cy5 / Cy7, etc.) cation and a counter ion (e.g., tetra(pentafluorophenyl)borate ion, acylated barbiturate ion, etc.). The precursor compound of the fluorescent ion pair includes a precursor compound providing the fluorescent ion (i.e., a fluorescent ion source) and a precursor compound providing the counter ion (i.e., a counter ion source).

[0036] The term "triphenylmethane compounds" as used herein refers to compounds whose molecular skeleton contains a triphenylmethane core. These triphenylmethane compounds include triphenylmethane dyes and their corresponding leuco forms. The triphenylmethane dyes (e.g., malachite green, crystal violet, methyl violet, brilliant green, Victoria Blue B, etc.) possess a highly conjugated π-electron system and exhibit characteristic absorption in the visible light region. The leuco forms (e.g., leuco malachite green, leuco crystal violet, etc.) do not possess a long-range conjugated system and therefore do not exhibit significant absorption in the visible light region. Unless otherwise specified, the term "triphenylmethane compounds" as used herein refers to triphenylmethane dyes by default; however, for the purposes of this application, the molecularly imprinted fluorescence sensor provided herein is also applicable to the detection of their leuco forms. When triphenylmethane dyes are used as the target for detection, the molecularly imprinted polymer directly uses this compound as the template molecule. When leuco forms are used as the target, the molecularly imprinted polymer uses the corresponding triphenylmethane dye as the template molecule. The detection of leuco forms typically requires sample pretreatment to quantitatively convert the leuco form into the corresponding colored dye before detection using the same method. The highly homologous chemical structures among triphenylmethane dyes provide feasibility for template molecule replacement.

[0037] The "cellulose filter paper" mentioned in this article refers to a porous sheet material made from plant fibers. The surface of cellulose filter paper contains abundant hydroxyl groups, providing reaction sites for the in-situ growth of molecularly imprinted polymers and the grafting of hydrophobic modifiers. Simultaneously, cellulose filter paper exhibits excellent chemical stability, maintaining its structural integrity without corrosion or dissolution in organic solvents such as acetonitrile and ethanol, and possesses extremely low background fluorescence, thus not interfering with fluorescence detection signals. As examples, cellulose filter paper includes, but is not limited to, qualitative filter paper, quantitative filter paper, and chromatography filter paper, with no particular restrictions on pore size distribution, and includes, but is not limited to, fast, medium-speed, and slow types. Specifically, qualitative filter paper typically has a cellulose purity greater than 95%, an α-cellulose content of over 98%, and an ash content generally not exceeding 0.13%; quantitative filter paper has an even lower ash content (typically ≤0.0009%); and chromatography filter paper has extremely high purity, uniform fibers, and a stable flow rate.

[0038] 2. Implementation Plan One embodiment of this application is as follows: A molecularly imprinted fluorescence sensor comprising a paper substrate and a composite functional coating; The composite functional coating contains molecularly imprinted polymers, fluorescent ion pairs, and an organic-inorganic hybrid network; The molecularly imprinted polymer uses triphenylmethane compounds as template molecules; The fluorescent ion pair forms a fluorescence resonance energy transfer system with the triphenylmethane compound; The organic-inorganic hybrid network is composed of a silica network and polymethyl methacrylate; The composite functional coating also contains grafted C 8-18 Silyl group.

[0039] In some specific implementations, the fluorescent ion pairs are loaded in the organic-inorganic hybrid network.

[0040] In some specific implementations, the molecularly imprinted polymer is distributed on the fiber surface of the paper substrate, and the molecularly imprinted polymer is partially or completely covered by the organic-inorganic hybrid network.

[0041] In some specific implementation schemes, the C 8-18 Silyl groups are grafted onto the surface of the molecularly imprinted polymer and / or the paper substrate.

[0042] In some specific implementation schemes, the C 8-18 The silane group is partially or completely covered by the organic-inorganic hybrid network.

[0043] In some specific implementations, the triphenylmethane compound is selected from any one of crystal violet, malachite green, methyl violet, brilliant green, and Victoria Blue B.

[0044] In some specific implementation schemes, the C 8-18 The silyl group is any one of octylsilyl, nonylsilyl, decylsilyl, undecylsilyl, dodecylsilyl, tridecylsilyl, tetradecylsilyl, pentadecylsilyl, hexadecylsilyl, heptadecanylsilyl, and octadecylsilyl.

[0045] In some specific embodiments, the molecularly imprinted polymer is formed from a polymerization system comprising functional monomers and crosslinking agents; The functional monomer is (3-aminopropyl)triethoxysilane; The crosslinking agent is tetraethoxysilane.

[0046] In some specific embodiments, the fluorescent ion pair consists of a rhodamine B cation and a tetra(pentafluorophenyl)borate ion.

[0047] In some specific embodiments, the paper substrate is cellulose filter paper, preferably qualitative filter paper, quantitative filter paper, or chromatography filter paper.

[0048] Another implementation scheme of this application is as follows: The preparation method of any of the aforementioned molecularly imprinted fluorescent sensors includes the following steps: S1. In situ polymerization is carried out on the surface of the paper substrate to obtain a molecularly imprinted polymer, and the template molecules are removed to obtain a first modified substrate; S2, using a silane coupling agent to connect C 8-18 Silane groups are grafted onto the surface of the first modified substrate to obtain a second modified substrate; S3. Load the fluorescent ion pair and the organic-inorganic hybrid network onto the second modified substrate to obtain the molecularly imprinted fluorescent sensor.

[0049] In some specific implementations, step S1 specifically includes the following steps: S11. Prepare a first mixture solution containing template molecules, functional monomers, crosslinking agents and catalysts; S12. The paper substrate is immersed in the first mixture solution to carry out a polymerization reaction; S13. After the polymerization reaction is completed, the template molecules are washed away and dried to obtain the first modified substrate; Preferably, the template molecule is crystal violet or malachite green, the functional monomer is (3-aminopropyl)triethoxysilane, and the crosslinking agent is tetraethoxysilane; Preferably, the molar ratio of the template molecule to the functional monomer is 1:3; Preferably, the molar ratio of the template molecule to the crosslinking agent is 1:10; Preferably, the solvent in the first mixture solution is a water / ethanol mixture; wherein the volume ratio of water to ethanol is preferably 1:1. Preferably, the catalyst in step S11 is ammonia water; Preferably, the polymerization reaction is carried out at room temperature; Preferably, the polymerization reaction lasts for 3-12 hours, more preferably 4 hours; Preferably, the template molecule is eluted with a methanol / acetic acid mixture.

[0050] In some specific implementations, step S2 specifically includes the following steps: S21. The first modified substrate is immersed in a solution containing a silane coupling agent to carry out a grafting reaction; S22. After the grafting reaction is completed, the physically adsorbed silane coupling agent is washed away, and the substrate is dried to obtain the second modified substrate. Preferably, the silane coupling agent is octadecyltrichlorosilane or octadecyltrimethoxysilane; Preferably, the volume fraction of the silane coupling agent in the solution used in step S21 is 1-5%, more preferably 3%; Preferably, the grafting reaction is carried out at 60°C; Preferably, the grafting reaction lasts for 10 minutes.

[0051] In some specific implementations, step S3 specifically includes the following steps: S31. Tetraethoxysilane is mixed with pure water, a catalyst is added, and a hydrolysis reaction is carried out to obtain silanol sol. S32. Prepare a second mixture solution containing fluorescent ion pairs and polymethyl methacrylate; S33. The silanol sol is mixed with the second mixture solution to obtain the third mixture solution; S34. After coating the third mixture solution onto the second modified substrate, heat treatment is performed to obtain the molecularly imprinted fluorescent sensor; Preferably, the volume ratio of the tetraethoxysilane to pure water is 2:1; Preferably, the catalyst in step S31 is hydrochloric acid; Preferably, the hydrolysis reaction lasts for 30 minutes; Preferably, the fluorescent ion source for the fluorescent ion pair is Rhodamine B; Preferably, the counter ion source for the fluorescent ion pair is tetra(pentafluorophenyl)borate; Preferably, the concentration of the fluorescent ion source in the second mixture solution is 1 mg / mL; Preferably, the concentration of polymethyl methacrylate in the second mixture solution is 10 mg / mL; Preferably, the molar ratio of the fluorescent ion source to the counter ion source is 1:1; Preferably, the solvent in the second mixture solution is acetonitrile; Preferably, the polymethyl methacrylate has a weight-average molecular weight of 50,000 to 350,000; Preferably, the coating method in step S34 is immersion or dripping; Preferably, the heat treatment is performed at 60°C for 10 minutes. Detailed Implementation

[0052] The raw materials used in this application can be purchased or synthesized in-house. The following specific embodiments are used to further describe the implementation of the present invention and do not limit the scope of the invention.

[0053] Example 1: Fabrication of an OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor This embodiment prepares the fluorescence sensor according to the following method: (1) TEOS pre-hydrolysis Measure 1.5 mL of tetraethoxysilane (TEOS) and 0.75 mL of pure water and mix them. While stirring continuously, add 0.15 mL of hydrochloric acid dropwise to the mixture. After the addition is complete, continue stirring at room temperature until a clear and homogeneous solution is formed, which is the TEOS pre-hydrolyzed sol (silanol sol).

[0054] (2) Preparation of fluorescent mother liquor Weigh out 0.01 g of Rhodamine B (RhB), 0.015 g of potassium tetra(pentafluorophenyl)borate (F5TPB), and 0.1 g of polymethyl methacrylate (PMMA). w = 100000 Da), dissolved in an appropriate amount of acetonitrile, and sonicated until completely dissolved and free of visible particles, to obtain the fluorescent mother liquor. The concentrations of PMMA, RhB, and F5TPB were 10 mg / mL, 1 mg / mL, and 1.5 mg / mL, respectively.

[0055] (3) Preparation of organic-inorganic hybrid network precursor / fluorescent ion pair mixture The fluorescent mother liquor was mixed with the TEOS pre-hydrolyzed sol, and the volume was adjusted to 10 mL with acetonitrile. The mixture was then gently stirred at 300 rpm under light-protected conditions to obtain the TEOS-PMMA@RhB-F5TPB solution, which was stored in the dark for later use.

[0056] (4) Preparation of filter paper modified with molecularly imprinted polymers (MIPs) 0.02 mmol of crystal violet (CV) was dissolved in 10 mL of water / ethanol (1:1 v / v) solution and vortexed to dissolve. 0.06 mmol of (3-aminopropyl)triethoxysilane (APTES) was added and mixed thoroughly. Then, 0.2 mmol of TEOS was added and mixed thoroughly to obtain the prepolymer solution. Ammonia was added dropwise to the prepolymer solution, and then a 12 mm diameter circular qualitative filter paper was placed in the polymerization solution and shaken on a shaker at room temperature for 4 hours. The filter paper was removed and air-dried to obtain molecularly imprinted polymer (MIPs) modified filter paper. The filter paper was washed with methanol / acetic acid (8:2 v / v) until CV was undetectable in the washing solution; then washed with methanol to remove acetic acid, and dried to obtain MIPs modified filter paper.

[0057] (5) Hydrophobic modification (silane grafting) The MIPs modified filter paper obtained in step (4) was immersed in a 3% volume fraction solution of octadecyltrichlorosilane (OTS) (solvent: anhydrous ethanol), then rinsed with anhydrous ethanol to remove physically adsorbed OTS, and dried in an oven at 60°C.

[0058] (6) Loading of the fluorescent layer and preparation of the final product The dried filter paper was immersed in the TEOS-PMMA@RhB-F5TPB solution prepared in step (3), then removed and placed horizontally in an oven for heat treatment (60°C, 10 min) to ensure complete condensation reaction, thus obtaining the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescent sensor of the present invention.

[0059] The aforementioned preparation and fixation processes were all carried out under light-protected conditions.

[0060] The construction principle of the fluorescence sensor is as follows: Figure 1 As shown.

[0061] Comparative Example 1: Fabrication of OTS / TEOS-PMMA@RhB-F5TPB NIPs fluorescence sensor Following the preparation method of Example 1, without adding CV, and with the other steps and conditions being the same, an OTS / TEOS-PMMA@RhB-F5TPB NIPs fluorescent sensor containing non-imprinted polymers (NIPs) was prepared.

[0062] Example 2: Fluorescence Analysis and Feasibility Verification The fluorescence spectra of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor were measured using a fluorescence spectrophotometer. The excitation wavelength was set to 560 nm, and the excitation and emission slit widths were set to 2.5 nm and 5.0 nm, respectively. During testing, a prepared filter paper was fixed to the surface of a magnetic chuck, and the magnetic chuck was placed in a quartz cuvette at a 45° angle for fluorescence spectral scanning. The fluorescence intensity at 590 nm was recorded, with the fluorescence intensity measured after adding ethanol solution recorded as F0 and the fluorescence intensity measured after adding 20 μL of CV solution recorded as F. The F0 / F value represents the fluorescence quenching efficiency of CV on RhB, and this quenching efficiency was used as an evaluation index to optimize various experimental conditions. Simultaneously, the fluorescence changes of the fluorescence sensor were recorded using a mobile phone under UV illumination.

[0063] To investigate the fluorescence response mechanism of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor, the fluorescence excitation and emission spectra of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor were measured. Figure 2As shown in Figure A, the maximum excitation wavelength of the fluorescence sensor is 560 nm. Under this wavelength excitation, a strong characteristic fluorescence emission peak is observed at 590 nm. The excitation and emission spectra exhibit typical Stokes shift characteristics, indicating that the fluorescent ion pair RhB-F5TPB has good fluorescence emission performance and can be used as a fluorescence signal source. Further comparisons were made in ethanol solution of the UV-Vis absorption spectrum of CV (10 μmol / L) and the fluorescence emission spectrum of RhB (1 mg / mL). Figure 2 (B) It was observed that the characteristic peak positions of the two are highly overlapping, and the strong absorption band of CV at 590 nm effectively overlaps with the emission spectrum of the MIPs fluorescence sensor, providing direct spectroscopic evidence for the occurrence of FRET. According to the fluorescence resonance energy transfer theory, when there is a significant overlap between the emission spectrum of the donor and the absorption spectrum of the acceptor (CV), the Förster radius R0 can be calculated by the following formula:

[0064] Where k 2 Φ is the dipole orientation factor; n is the refractive index of the solvent; Φ D Let RhB be the quantum yield; J be the spectral overlap integral, defined by the following equation:

[0065] In the formula, F D (λ) represents the normalized fluorescence emission spectrum of the donor (RhB); ε A (λ) represents the molar absorptivity of the acceptor (CV) at wavelength λ, where λ is the wavelength. Substituting the relevant spectral data, the Förster radius R0 of CV and RhB is calculated to be 6.76 nm, proving that the effective interaction range between the donor and acceptor is 1–10 nm. At this point, the excited-state energy of the donor can be transferred to the acceptor through nonradiative dipole-dipole coupling, resulting in donor fluorescence quenching and enhanced acceptor absorption signal, thus putting the system in a fluorescence "off" state.

[0066] The same concentration (5 μmol / L) of CV was added to the MIPs fluorescence sensor prepared in Example 1 and the NIPs fluorescence sensor prepared in Comparative Example 1, respectively, for fluorescence spectroscopy analysis. The results are as follows: Figure 3As shown, MIPs, using CV as a template molecule during preparation, form imprinted holes with specific recognition capabilities, enabling selective recognition of CV. The fluorescence intensity of the MIPs fluorescence sensor significantly decreased after the addition of the target molecule, resulting in a fluorescence quenching efficiency (F0 / F) of 2.40 (where F0 is the initial fluorescence intensity measured by the sensor without the analyte; F is the fluorescence intensity measured by the sensor after the analyte is added). In contrast, NIPs, without the introduction of a template molecule during synthesis, primarily exhibit non-specific CV adsorption, leading to an F0 / F ratio of only 1.56 for the NIPs fluorescence sensor. These results demonstrate that the fluorescence signal variation amplitude of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor of this invention is significantly higher than that of the OTS / TEOS-PMMA@RhB-F5TPB NIPs fluorescence sensor, exhibiting excellent recognition performance and detection feasibility for CV.

[0067] Example 3: Investigation of Modification Strategies The PMMA@RhB-F5TPB MIPs fluorescent sensor was obtained by referring to the preparation method of Example 1, but without using OTS modification and without using TEOS pre-hydrolyzed sol in step (3), and with the other conditions being the same.

[0068] Following the preparation method of Example 1, but without using OTS modification, and with all other conditions remaining the same, a TEOS-PMMA@RhB-F5TPB MIPs fluorescent sensor was obtained.

[0069] The OTS-PMMA@RhB-F5TPB MIPs fluorescent sensor was obtained by referring to the preparation method of Example 1, but without using TEOS pre-hydrolyzed sol in step (3).

[0070] The three aforementioned fluorescence sensors were placed side-by-side with the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor prepared in Example 1. 20 μL of anhydrous ethanol was added to the center region of each filter paper, and the fluorescence changes were observed after standing. The experimental results are as follows: Figure 4As shown, under UV light (365 nm), the control group filter paper without silanization modification exhibited significant fluorescence quenching in the ethanol-wetted area. While the filter paper modified with TEOS or OTS alone showed some improvement, varying degrees of fluorescence attenuation were still observed, and the area where ethanol was added showed whitening under fluorescent light, indicating that its fluorescent layer was eroded by ethanol. In contrast, the PMMA@RhB-F5TPB MIPs filter paper synergistically modified with OTS / TEOS maintained its original morphology under both UV light and fluorescent light after ethanol addition, without significant attenuation or whitening. This phenomenon indicates that the synergistic modification of OTS / TEOS significantly improves the fluorescence sensor's resistance to organic reagent erosion; specifically, TEOS provides a rigid silicon-oxygen framework to enhance structural stability, while OTS introduces long-chain alkyl groups to provide a hydrophobic barrier. The synergistic effect of both effectively blocks the dissolution of fluorescent dyes by ethanol.

[0071] Example 4: Scanning Electron Microscopy Characterization To characterize the microstructure of the fluorescence sensors and verify the formation of the molecular imprint structure, scanning electron microscopy (SEM) was used to characterize the morphology of blank filter paper and the three fluorescence sensors prepared above: TEOS-PMMA@RhB-F5TPB MIPs, OTS-PMMA@RhB-F5TPB MIPs, and OTS / TEOS-PMMA@RhB-F5TPB MIPs. Figure 5 (A) shows that the surface of the blank filter paper exhibits a layered, interwoven fiber structure. Figure 5 (B), (C) and (D) show that spherical particles are distributed on the fiber surface of the filter paper, indicating that the molecular imprints have been successfully attached to the paper substrate surface; among them, the filter paper fibers of OTS / TEOS-PMMA@RhB-F5TPB MIPs are more tightly wrapped in the hydrophobic barrier, indicating that the filter paper structure of OTS / TEOS-PMMA@RhB-F5TPB MIPs is more robust.

[0072] Example 5: Selective Investigation To verify the specific recognition capability of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor for catalytic corrosion (CV), a series of potentially coexisting, structurally similar, or functionally different prohibited or restricted aquatic drugs were selected as comparisons, including: malachite green (MG), leucomalle green (LMG), leuco crystal violet (LCV), methyl violet (MV), brilliant green (BG), chloramphenicol (CAP), nitrofuran (NF), and sulfamethoxypyrimidine (SMD). Equal concentrations of 5 μM CV and each competitor solution were added dropwise to the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor and a control NIPs fluorescence sensor (prepared as Comparative Example 1), and the changes in fluorescence intensity were measured. The fluorescence quenching efficiency was calculated to evaluate the response of the fluorescence sensor to different analytes. Furthermore, the selectivity of the MIPs filter paper for CV relative to each competitor, and the relative selectivity between the MIPs and NIPs fluorescence sensors, were calculated to quantitatively characterize the high selectivity of the MIPs fluorescence sensor of this invention for CV.

[0073] like Figure 6 As shown, under the same testing conditions, the fluorescence quenching efficiency induced by CV on the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor was significantly higher than that of all other control substances. This is because, during the synthesis of MIPs, the imprinted holes formed using CV as a template can selectively capture target molecules and efficiently quench the emission signal of the RhB-F5TPB fluorescent ion pair through a fluorescence resonance energy transfer mechanism. In contrast, the OTS / TEOS-PMMA@RhB-F5TPB NIPs fluorescence sensor did not show significant differences in fluorescence quenching for any of the test substances.

[0074] The above results demonstrate that the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescent sensor prepared using CV as a template exhibits excellent molecular recognition capability and anti-interference performance for CV. It is anticipated that the technical solution provided in this application is also applicable to other triphenylmethane compounds (such as malachite green MG, methyl violet MV, and brilliant green BG); simply by replacing the template molecule with the target analyte, the corresponding molecularly imprinted fluorescent sensor can be prepared under the same synthetic system, achieving specific detection of the target analyte.

[0075] Example 6: Linear Analysis Different concentrations of colorimetric fluorescence (CV) were detected and analyzed using an OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor. Figure 7 As shown in A and 7C, the fluorescence intensity of the MIPs fluorescence sensor decreases systematically with increasing CV concentration. Figure 7B shows that the F0 / F ratio increases with increasing CV concentration. Stern-Volmer curves were plotted using the relationship between F0 / F and CV concentration. The results show a good linear relationship in the concentration range of 0.1–20 μmol / L, with the linear regression equation being F0 / F = 1.0591 + 0.1413 [C], and the correlation coefficient R0. 2 = 0.9905, indicating that the sensor has quantitative analysis capability within this concentration range, and the method's limit of detection (LOD) is 0.040 μmol / L.

[0076] Example 7: Stability Analysis The fluorescence stability of the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor was studied by placing it for different periods of time. The results are as follows: Figure 8 As shown in Figure A, under ultraviolet light, the fluorescence intensity of the filter paper did not change significantly from the initial fluorescence intensity within 10 hours as the storage time increased. Subsequently, after continuous storage in the dark environment for 30 days... Figure 8 (B) The fluorescence intensity of the fluorescence sensor still retains 89.31% of the original fluorescence intensity, indicating that the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor of the present invention has good fluorescence stability.

[0077] Example 8: Actual Sample Testing Fresh grass carp and prawns were used as samples, and CV (capillary oxidase) was extracted and purified from the samples according to the method specified in the National Standard of the People's Republic of China GB / T 19857—2005. Table 1 shows the detection results of CV residues in aquatic products using the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor. The spiked recovery rate of this method was 84.06%~94.34% (RSD: 0.95%~6.65%), indicating that the OTS / TEOS-PMMA@RhB-F5TPB MIPs fluorescence sensor of this invention can be used to detect CV residues in actual samples.

[0078] Table 1. Detection of CV in actual samples

[0079] Example 9: Optimization of preparation conditions Example 9.1: Optimization of OTS Concentration Molecularly imprinted filter paper was immersed in OTS solutions with volume fractions of 1%, 2%, 3%, 4%, and 5%, respectively, and its fluorescence intensity and fluorescence quenching response were measured. Figure 9As can be seen from Figure A, when the OTS volume fraction is in the range of 1% to 3%, the fluorescence intensity of the fluorescence sensor increases slightly with increasing OTS content, reaching a peak at 3%, with a relatively small overall change. However, when the OTS volume fraction is further increased to 4% or higher, the fluorescence intensity decreases significantly. Figure 9 The fluorescence quenching efficiency (F0 / F) results for B show that the quenching response reaches its maximum at 3%, and then decreases with increasing OTS volume fraction. This phenomenon may be because low volume fraction OTS forms a thin hydrophobic monolayer on the fiber surface, which can stabilize the fluorescence microenvironment, reduce non-radiative transition losses, and maintain the exposure of imprinted sites, thus gradually improving both fluorescence signal and quenching efficiency. When the OTS volume fraction is too high, the excessive hydrophobic layer will encapsulate the voids in the filter paper fiber structure, hindering fluorescence loading and target mass transfer, resulting in a significant decrease in fluorescence intensity and sensing performance.

[0080] Example 9.2: Eluent Optimization Elution was performed using ethanol / acetonitrile (8:2), methanol, methanol / acetic acid (9:1), and methanol / acetic acid (8:2) in the same volume, respectively. Figure 10 As shown in Figure A, the elution ability of ethanol / acetonitrile (8:2) and methanol for template molecules using CV was weak, almost ineffective, resulting in a weak fluorescence signal; while methanol / acetic acid (9:1) and methanol / acetic acid (8:2) both showed better elution effects. Further evaluation of recognition performance was conducted by adding CV solutions of the same concentration to assess their fluorescence quenching efficiency. Figure 10 As shown in Figure B, the fluorescence quenching efficiency was highest when methanol / acetic acid (8:2) was used as the eluent, indicating that more cells were formed in the blot under this condition, resulting in a stronger ability to recognize the target. Therefore, methanol / acetic acid (8:2) was chosen as the CV template eluent.

[0081] Example 9.3: Optimization of TEOS Addition Amount The effects of TEOS addition amounts (0.5, 1.0, 1.5, 2.0, 2.5 mL) on fluorescence performance and detection sensitivity were investigated. Figure 11As shown in Figure A, the initial fluorescence intensity of the fluorescent hybrid film gradually increased with the addition of TEOS from 0.5 mL to 1.5 mL. The fluorescence intensity reached its maximum when the TEOS addition reached 1.5 mL; further increases in TEOS did not significantly improve the fluorescence intensity, but a significant decrease occurred when the addition reached 2.5 mL. This was due to excessive cross-linking caused by excessive TEOS, resulting in the fluorescent ion pairs being encapsulated by the dense silicon-based network and the luminescent groups being shielded. The silica network formed by the hydrolysis and condensation of an appropriate amount of TEOS can effectively encapsulate the RhB-F5TPB fluorescent ion pairs, providing a stable and rigid microenvironment for the dye molecules, reducing dye leakage during curing and subsequent processing, thereby enhancing fluorescence output. Simultaneously, the quenching efficiency was investigated. Figure 11 B illustrates the fluorescence quenching response of the fluorescence sensor to CV under different TEOS addition amounts. The sensor exhibits the highest fluorescence quenching efficiency when the TEOS addition amount is 1.5 mL. The quenching efficiency is lower when the TEOS addition amount is 0.5 mL and 1.0 mL, possibly due to the insufficient density of the inorganic network structure, making the fluorescent units easily washed away or migrated by the solvent during detection, resulting in an insufficient number of effective quenching centers. When the TEOS addition amount increases to 2.0 mL and above, the excessively dense network structure, while enhancing the stability of the fluorescent units, may also hinder the diffusion of CV molecules to the recognition site, increasing mass transfer resistance and thus leading to a decrease in quenching efficiency.

[0082] Example 9.4: Optimization of TEOS pre-hydrolysis time The effect of TEOS pre-hydrolysis time (5, 15, 30, 60 min) on the CV detection performance of the fluorescence sensor was investigated, and the results are as follows: Figure 12As shown in the figure. Experimental results indicate that the pre-hydrolysis time of TEOS has a significant impact on the fluorescence quenching efficiency of the sensor. When the hydrolysis time is 5 min, the quenching efficiency of the sensor is low; when the hydrolysis time reaches 30 min, the sensor exhibits the highest fluorescence quenching efficiency; further extending the hydrolysis time to 60 min, the quenching efficiency shows a significant downward trend. This phenomenon can be attributed to the regulatory effect of the degree of TEOS hydrolysis and condensation on the microstructure of the hybrid network. When the hydrolysis time is short (5~15 min), TEOS hydrolysis is incomplete, the active silicon content in the system is low, and the inorganic network structure formed by subsequent condensation is relatively loose, resulting in insufficient embedding of RhB-F5TPB fluorescent ion pairs. During the detection process, some fluorescent units may migrate or leak due to solvent erosion, thus exhibiting a low quenching efficiency. When the hydrolysis time is extended to 30 min, TEOS reaches a moderate hydrolysis, forming a sufficient number of active silanols, which can construct a relatively complete and uniform organic-inorganic hybrid network in the subsequent condensation process. This network structure effectively immobilizes fluorescent ion pairs, preventing their loss during detection and thus achieving optimal fluorescence quenching response. However, when the hydrolysis time is too long (60 min), the TEOS hydrolysis products undergo excessive condensation, potentially forming large silica particles or prepolymers. This reduces compatibility with the PMMA / acetonitrile organic phase, leading to microscopic phase separation or film inhomogeneity in the hybrid system. While an overly dense network structure enhances the stability of fluorescent ion pairs, it may also hinder the diffusion of CV molecules to the recognition site, resulting in decreased quenching efficiency. Considering the overall trend of fluorescence quenching efficiency, the sensor achieves optimal CV detection performance when the TEOS pre-hydrolysis time is 30 min.

[0083] Example 9.5: PMMA Concentration Optimization The effect of PMMA concentration (5, 10, 15, 20 mg / mL) on the performance of the sensor's composite functional coating was investigated. Figure 13As shown in Figure A, the initial fluorescence intensity of the sensor showed a significant upward trend as the PMMA concentration increased from 5 mg / mL to 10 mg / mL. However, the increase in fluorescence intensity plateaued after the PMMA concentration exceeded 10 mg / mL, with no significant difference in fluorescence intensity between the 15 mg / mL and 20 mg / mL samples compared to the 10 mg / mL concentration. This phenomenon can be attributed to the dual role of PMMA in the hybrid system: firstly, as a film-forming polymer, PMMA effectively encapsulates the RhB-F5TPB fluorescent ion pair, reducing leakage and aggregation quenching of dye molecules during curing and subsequent processing; secondly, the introduction of an appropriate amount of PMMA improves the compatibility between the silica inorganic network and the organic fluorescent components, thereby enhancing fluorescence output. When the PMMA concentration reached 10 mg / mL, the encapsulation of the fluorescent unit tended to saturate, and further increasing the PMMA concentration only slightly altered the film thickness or refractive index, contributing little to the improvement of fluorescence intensity. Further investigation of the fluorescence sensor's response performance to CV at different PMMA concentrations yielded the following results: Figure 13 As shown in B, the sensor exhibited the highest fluorescence quenching efficiency at a PMMA concentration of 10 mg / mL. At a PMMA concentration of 5 mg / mL, the quenching efficiency was lower, possibly because the polymer network was insufficient to completely encapsulate the fluorescent units, exposing some dye to the rigid inorganic network and resulting in an insufficient number of effective quenching centers. Furthermore, when the PMMA concentration increased to 15 mg / mL and 20 mg / mL, the excessively dense network structure may have hindered the diffusion of CVs to the recognition sites, leading to increased mass transfer resistance and a slight decrease in quenching efficiency.

Claims

1. A molecularly imprinted fluorescence sensor comprising a paper substrate and a composite functional coating; The composite functional coating contains molecularly imprinted polymers, fluorescent ion pairs, and an organic-inorganic hybrid network; The molecularly imprinted polymer uses triphenylmethane compounds as template molecules; The fluorescent ion pair forms a fluorescence resonance energy transfer system with the triphenylmethane compound; The organic-inorganic hybrid network is composed of a silica network and polymethyl methacrylate; The composite functional coating also contains grafted C 8-18 Silyl group.

2. The molecularly imprinted fluorescence sensor according to claim 1, characterized in that, The triphenylmethane compound is selected from any one of crystal violet, malachite green, methyl violet, brilliant green, and Victoria Blue B.

3. The molecularly imprinted fluorescence sensor according to claim 1, characterized in that, The C 8-18 The silyl group is any one of octylsilyl, nonylsilyl, decylsilyl, undecylsilyl, dodecylsilyl, tridecylsilyl, tetradecylsilyl, pentadecylsilyl, hexadecylsilyl, heptadecanylsilyl, and octadecylsilyl.

4. The molecularly imprinted fluorescence sensor according to claim 1, characterized in that, The molecularly imprinted polymer is formed from a polymerization system comprising functional monomers and crosslinking agents; The functional monomer is (3-aminopropyl)triethoxysilane; The crosslinking agent is tetraethoxysilane.

5. The molecularly imprinted fluorescence sensor according to claim 1, characterized in that, The fluorescent ion pair is composed of a fluorescent dye cation and a counter ion; Preferably, the fluorescent dye is rhodamine B, octadecylrhodamine B, or anthocyanin; Preferably, the counter ion is tetra(pentafluorophenyl)borate ion or acylated barbiturate ion; More preferably, the fluorescent ion pair is composed of a rhodamine B cation and a tetra(pentafluorophenyl)borate ion.

6. The molecularly imprinted fluorescence sensor according to claim 1, characterized in that, The paper substrate is cellulose filter paper, preferably qualitative filter paper, quantitative filter paper or chromatography filter paper.

7. The method for preparing the molecularly imprinted fluorescent sensor as described in claim 1, characterized in that, Includes the following steps: S1. In situ polymerization is carried out on the surface of the paper substrate to obtain a molecularly imprinted polymer, and the template molecules are removed to obtain a first modified substrate; S2, using a silane coupling agent to connect C 8-18 Silane groups are grafted onto the surface of the first modified substrate to obtain a second modified substrate; S3. Load the fluorescent ion pair and the organic-inorganic hybrid network onto the second modified substrate to obtain the molecularly imprinted fluorescent sensor.

8. The preparation method according to claim 7, characterized in that, Step S1 specifically includes the following steps: S11. Prepare a first mixture solution containing template molecules, functional monomers, crosslinking agents and catalysts; S12. The paper substrate is immersed in the first mixture solution to carry out a polymerization reaction; S13. After the polymerization reaction is completed, the template molecules are washed away and dried to obtain the first modified substrate; Preferably, the template molecule is crystal violet or malachite green, the functional monomer is (3-aminopropyl)triethoxysilane, and the crosslinking agent is tetraethoxysilane; Preferably, the molar ratio of the template molecule to the functional monomer is 1:3; Preferably, the molar ratio of the template molecule to the crosslinking agent is 1:10; Preferably, the solvent in the first mixture solution is a water / ethanol mixture; wherein the volume ratio of water to ethanol is preferably 1:

1. Preferably, the catalyst in step S11 is ammonia water; Preferably, the polymerization reaction is carried out at room temperature; Preferably, the polymerization reaction lasts for 3-12 hours, more preferably 4 hours; Preferably, the template molecule is eluted with a methanol / acetic acid mixture.

9. The preparation method according to claim 7, characterized in that, Step S2 specifically includes the following steps: S21. The first modified substrate is immersed in a solution containing a silane coupling agent to carry out a grafting reaction; S22. After the grafting reaction is completed, the physically adsorbed silane coupling agent is washed away, and the substrate is dried to obtain the second modified substrate. Preferably, the silane coupling agent is octadecyltrichlorosilane or octadecyltrimethoxysilane; Preferably, the volume fraction of the silane coupling agent in the solution used in step S21 is 1-5%, more preferably 3%; Preferably, the grafting reaction is carried out at 60°C; Preferably, the grafting reaction lasts for 10 minutes.

10. The preparation method according to claim 7, characterized in that, Step S3 specifically includes the following steps: S31. Tetraethoxysilane is mixed with pure water, a catalyst is added, and a hydrolysis reaction is carried out to obtain silanol sol. S32. Prepare a second mixture solution containing fluorescent ion pairs and polymethyl methacrylate; S33. The silanol sol is mixed with the second mixture solution to obtain the third mixture solution; S34. After coating the third mixture solution onto the second modified substrate, heat treatment is performed to obtain the molecularly imprinted fluorescent sensor; Preferably, the volume ratio of the tetraethoxysilane to pure water is 2:1; Preferably, the catalyst in step S31 is hydrochloric acid; Preferably, the hydrolysis reaction lasts for 30 minutes; Preferably, the fluorescent ion source for the fluorescent ion pair is Rhodamine B; Preferably, the counter ion source for the fluorescent ion pair is tetra(pentafluorophenyl)borate; Preferably, the concentration of the fluorescent ion source in the second mixture solution is 1 mg / mL; Preferably, the concentration of polymethyl methacrylate in the second mixture solution is 10 mg / mL; Preferably, the molar ratio of the fluorescent ion source to the counter ion source is 1:1; Preferably, the solvent in the second mixture solution is acetonitrile; Preferably, the polymethyl methacrylate has a weight-average molecular weight of 50,000 to 350,000; Preferably, the coating method in step S34 is immersion or dripping; Preferably, the heat treatment is performed at 60°C for 10 minutes.